Application of citral as an antifungal agent in the control of postharvest diseases of citrus fruits: A review - Houda El Kahia; Ezzouhra El Maaiden; Kawtar Farih; Zahid Abderrakib; Majid Mounir; Hafsa Korri-Youssoufi; Lamfeddal Kouisni; Youssef El Kharrassi (Journal of Agriculture and Food Research)
Citrus fruits are highly susceptible to fungal infections during storage due to their elevated moisture and nutrient content, leading to reduced shelf life and significant economic losses. For years, postharvest diseases in citrus have been managed with synthetic fungicides. However, due to their harmful effects on human health and environmental toxicity, the search for safer alternative solutions for managing these diseases has become imperative. Natural products including essential oils (EO) have been proposed as alternative methods to control plant pathogens and pests, as well as for post-harvest applications. Citral has been identified as the most potent antifungal compound found in the essential oils of citrus, and lemon-scented plants. This valuable compound was reported in several studies to be effective against major citrus postharvest pathogens, mainly Penicillium digitatum, Penicillium italicum, and Geotrichum candidum, which are responsible, respectively, for green mold, blue mold, and sour rot. Therefore, this review explores methods used for the extraction and isolation of citral from citral-rich plants, its antifungal mechanism against citrus pathogens, and the challenges associated with its application, such as volatility, instability, low water solubility, and potential phytotoxicity on fruit skin. Additionally, the review highlights recent advancements in incorporating citral into coating formulations to mitigate postharvest losses and preserve citrus fruit quality.